Effects of Sanitizers on Microbiological Control of Hatching Eggshells and Poultry Health during Embryogenesis and Early Stages after Hatching in the Last Decade - Gabriel da Silva Oliveira; Concepta McManus; Cristiane Batista Salgado; Vinícius Machado dos Santos (Animals, 2022)
The sanitization of hatching eggs is the backbone of the hygienic–sanitary management of eggs on farms and extends to the hatchery. Poultry production gains depend on the benefits of sanitizers. Obtaining the maximum yield from incubation free of toxic sanitizers is a trend in poultry farming, closely following the concerns imposed through scientific research. The toxic characteristics of formaldehyde, the primary sanitizer for hatching eggs, are disappointing, but it is a cheap, practical and widely used antimicrobial. To overcome this shortcoming, multiple synthetic and natural chemical sanitizers have been, and continue to be, tested on hatching eggs. This review aims to evaluate the effects of different sanitizers on the microbiological quality of hatching eggshells and poultry health during embryogenesis and early stages after hatching.